Comparison Anticancer Effects of Platinum Ribavirin with Platinum Azidothymidine via Telomerase, Bcl-2, miRNA-21 and miRNA-122 Biomarkers Genes Expression on HepG2 Cancer Cell Lines - Abdolreza Sabokrouh; Nasim Ghaffari; Soheila Hajivand; Fereshteh Atabi; Reza Saghiri; Zohreh Sharifi (Middle East Journal of Cancer, 2025)
Background: Anticancer medication assessment is performed by numerous approaches including biomarkers gene expression. This study aimed to investigate the anticancer effects of Pt-Rb and Pt-AZTon HepG2 cells. Method: In this case-control study, four groups of cells were examined. Group A was the control group, group B was untreated cancer cells, and Groups C and D were treated with Pt-AZT and Pt-Rb, respectively. Using the MTT test, LC50 was determined, and the relative gene expression of the biomarkers was assessed by RNA extraction, cDNA synthesis and RT-PCR. Through histopathlogical study apoptotic regions of cells were compared. Data analysis was done using ANOVA and Turkey’s post hoc test.Results: The results showed a significant increase for the proapoptotic gene miRNA-122 (19.97 ± 0 .04) in group D compared with group C (10.36 ± 0.007). Also, there was a significant decrease in the antiapoptotic genes in group D, including miRNA-21 (0.10 ± 0.014), telomerase (0.56 ± 0.480), and Bcl-2 (0.41 ± 0.276), compared with group C (miRNA-21: 2.0 ± 0.145, telomerase: 2.49 ± 0.231, and Bcl-2: 2.93 ± 0.276). There were significant differences between the nearly all studied groups (P < 0.05). There were more extensive apoptotic regions in group D compared with group C.Conclusion: Using Pt-Rb has more benefits in terms of stronger anticancer effects than Pt-AZT on cancer cells. Also, lower drug resistance and lower side effects in Pt-Rb were considered compared with Pt-AZT, indicating that it can be more effective in anti-cancer therapy.